Komunikasi Digital PT. Marga Mandala Sakti dalam Meningkatkan Pelayanan Masyarakat pada Pengguna Tol: Studi Kasus Gerbang Tol Serang - Intan Nabila Azhar; April Laksana; Putri Handayani; Achmad Nashrudin; Meiby Zulfikar (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effectiveness of PT. Marga Mandala Sakti's digital communication to improve public services for toll road users through the implementation of digital communication. PT. Marga Mandala Sakti's non-cash payment service, Tapcash, was used in this study using descriptive qualitative methods and case studies. Data collection techniques included interviews, observation, and documentation with four informants selected using purposive sampling. The theory used was digital communication. The results show that PT. Marga Mandala Sakti's digital communication is effective and well-supported by users of the Tangerang-Merak toll road. The innovation and launch of this digital-based application have received a positive response from toll road users. Although many remain unaware, PT. Marga Mandala Sakti continues to strive to introduce and enhance its customer service products. The benefits (value) of digitalization increase efficiency and convenience, but there are criticisms calling for a downloadable application to facilitate access. Furthermore, service limitations, technical issues such as server disruptions, and low public participation reduce its effectiveness.